Self-regulation of sustainability as a manifestation of corporate social responsibility - López Jiménez, David; Dittmar, Eduardo Carlos; Vargas Portillo, Jenny Patricia (Revista de Ciencias Sociales, 2021)
Corporate social responsibility is a phenomenon that can have an impact on many areas of social life, such as sustainability. In this article, we examine corporate social responsibility and analyse the repercussions considered in environmental matters. We specifically consider self-regulation as a business instrument for promoting best practices in this area. Notwithstanding the particularities of this tool, we pay special attention to the thought-provoking role of self-regulation from a legal-business perspective in this field. Although this decision is an a priori voluntary decision, we assume that self-reflection entails mandatory commitments undertaken in the area of sustainability.